ROLE OF STEM CELL FACTOR IN THE REACTIVATION OF HUMAN FETAL HEMOGLOBIN - Ugo Testa; Marco Gabbianelli (Mediterranean Journal of Hematology and Infectious Diseases)
In humans the switch from fetal to adult hemoglobin (HbF→ HbA) takes place in the perinatal and postnatal period, determining the progressive replacement of HbF with HbA synthesis ( i.e., the relative HbF content in red blood cells decreases from 80-90% to <1%). In spite of more than twenty years of intensive investigations on this classic model, the molecular mechanisms regulating the Hb switching, as well as HbF synthesis in adults, has been only in part elucidated. In adult life, the residual HbF, restricted to F cell compartment, may be reactivated up to 10-20% of total Hb synthesis in various conditions associated with “stress erythropoiesis”: this reactivation represented until now an interesting model of partial Hb switch reverse with important therapeutic implications in patients with hemoglobinopathies, and particularly in -thalassemia. In vitro and in vivo models have led to the identification of several chemical compounds able to reactivate HbF synthesis in adult erythroid cells. Although the impact of these HbF inducers, including hypomethylating agents, histone deacetylase inhibitors and hydroxyurea, was clear on the natural history of sickle cell anemia, the benefit on the clinical course of -thalassemia was only limited: particularly, the toxicity and the modest increase in γ-globin reactivation indicated the need for improved agents able to induce higher levels of HbF. In the present review we describe the biologic properties of Stem Cell Factor (SCF), a cytokine sustaining the survival and proliferation of erythroid cells, that at pharmacological doses acts as a potent stimulator of HbF synthesis in adult erythroid cells.